Synthetic approaches, emerging applications, and challenges of indole-based five-membered heterocycles in medicinal chemistry - M. Padmapriya; Sushruta S. Hakkimane; Santosh L. Gaonkar (Discover Applied Sciences)
Abstract Scientists are fascinated by the indole structure due to its diverse biological activities, encompassing both indole itself and its numerous substituted derivatives. Heterocycles, particularly those containing indoles, play pivotal roles in the domains of medicinal chemistry, drug designing and discovery, agrochemicals, photochemistry, dyes, and other applications, which has led to their prominence in the chemistry field. This review highlights the diverse applications of indole-based five-membered heterocycles as versatile scaffolds for drug development, emphasizing their therapeutic potential as antidiabetic, anti-inflammatory, anticancer, antimicrobial, antioxidant agents, antialzheimer and anticonvulsant agents. A comprehensive literature search was carried out to explore the chemical, biological, and structural activity correlations of indole-based hybrids. Studies published between 2017 and 2024 were chosen from databases such as PubMed, Scopus and Google Scholar, emphasizing the synthesis, activity and application of indole-based heterocycles in medicinal chemistry. Unique to this review is the exploration of structure–activity relationships (SAR), synthetic approaches and emerging challenges in the development of indole-based drugs. Key insights include innovative strategies to enhance biological efficacy through structural modifications and various applications of indole-based derivatives in therapeutic areas. These findings hold great potential for improving the design of more effective pharmaceuticals. Graphical abstract